2017
DOI: 10.1039/c7tc03700g
|View full text |Cite
|
Sign up to set email alerts
|

MoO3-induced oxidation doping of PEDOT:PSS for high performance full-solution-processed inverted quantum-dot light emitting diodes

Abstract: MoO3-induced oxidation in PEDOT:PSS hole contact enables improving its conductivity, work function and process compatibility for application in solution-processed transparent QD-LEDs, attaining a maximum luminous efficiency of 1.39 cd A−1and a transparency of >70%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 34 publications
3
36
0
Order By: Relevance
“…The 5-nm thick s-MoO 3 layer assists the deposition of composite anode on the hydrophobic PVK layer (30 nm). 28 These functional layers were spin-coated via a layer-by-layer approach on the surface of the pre-patterned ITO/glass substrates. ZnO ETL was formed on ITO/glass by spin coating at a rotation speed of 2000 rpm for 40 s, following an annealing at 150°C for 10 min in the glove box.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 5-nm thick s-MoO 3 layer assists the deposition of composite anode on the hydrophobic PVK layer (30 nm). 28 These functional layers were spin-coated via a layer-by-layer approach on the surface of the pre-patterned ITO/glass substrates. ZnO ETL was formed on ITO/glass by spin coating at a rotation speed of 2000 rpm for 40 s, following an annealing at 150°C for 10 min in the glove box.…”
Section: Methodsmentioning
confidence: 99%
“…27 However, deposition of the PEDOT:PSS-based composite upper anode had some process difficulties due to the poor wettability of the aqueous PEDOT:PSS on hydrophobic surface of the organic HTL. In a recent work, 28 we demonstrated that the use of solution-processed molybdenum trioxide (s-MoO 3 ) additive in the composite PEDOT:PSS/ AgNWs anode greatly improves its process wettability and contact quality at the QD emission layer/upper anode interface. It is shown that the addition of s-MoO 3 nanoparticles (NPs) not only alleviates the deposition difficulty of the upper composite anode but also enhances the hole injection at the QD emissive layer/upper anode interface.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al . also reported on MoO 3 and PEDOT : PSS hybrid electrode for transparent inverted QDLEDs.…”
Section: Transparent Conducting Electrodes For Quantum Dots Light Emimentioning
confidence: 98%
“…Lee et al [137] also reported on MoO 3 and PEDOT: PSS hybrid electrode for transparent inverted QDLEDs. The aqueous MoO 3 additive in conductive PEDOT: PSS improved the hole injection and wettability of the PEDOT: PSS surface.…”
Section: Hybrid Electrodes For Qdledsmentioning
confidence: 99%